Rape as a Practice of War: Toward a Typology of Political Violence. (December 2018) - Wood, Elisabeth Jean
When rape by an armed organization occurs frequently, it is often said to be a strategy of war. But some cases of conflict-related rape are better understood as a practice, violence that has not been explicitly adopted as organization policy but is nonetheless tolerated by commanders. The typology of conflict-related rape in this article emphasizes not only vertical relationships between commanders (principals) and combatants (agents) but also the horizontal social interactions among combatants. It analyzes when rape is likely to be prevalent as a practice, emphasizing not only gendered norms and beliefs of the society from which combatants come but also how those might be transformed by the organization's socialization processes. In the conclusion, I suggest that the typology is relevant for analysts of all forms of of political violence and also for prosecutors, policy advocates, and policymakers concerned with conflict-related rape.